Preparation and Characterization of TiO2 Nanofluid by Sol-gel Method for Cutting Tools - Birlik, Işıl; Ak Azem, N. Funda; Yiğit, Recep; Erol, Mustafa; Yıldırım, Serdar; Yurddaşkal, Metin; Sancakoğlu, Orkut; Çelik, Erdal (Afyon Kocatepe Üniversitesi, 2014)
In the past few decades, rapid advances in nanotechnology have lead to emerging of new generation of coolants called as nanofluids. Nanofluids are defined as suspension of nanoparticles in a basefluid. Machining experiences high temperatures due to friction between the tool and workpiece, thus influencing the workpiece dimensional accuracy and surface quality. Further, the cutting fluids also incur a major portion of the total manufacturing cost. Nanofluids are containing oxides including MgO, TiO2, ZnO, Al2O3 and SiO2 nanoparticles. Nanofluids are produced by dispersing nanometer scale solid particles into base liquids such as water, ethylene glycol or oil. In this study, TiO2 nanoparticles were produced by using sol-gel technique and TiO2 the nanoparticles were suspended in a specified volume of the base fluid. Regarding the analysis of materials, phase analysis was determined by using X-ray diffactometer (XRD) and the average particle size distribution (APS) using particle size analyzer. The present study summarizes the effect of nanofluid with TiO2 nanoparticles on the performance of the cutting tools.
Kesici Takımlar İçin Sol-jel Metoduyla TiO2 Nanosıvıların Hazırlanması ve Karakterizasyonu
Keywords: Nanofluid; Nanoparticle; Sol-gel Method; Milling; Cutting Tools; TiO2